Pencak silat Seliwa Betawi: A review in the perspective of historical development in Palembang - Saputra, Muhammad Nanda; Riyoko, Endie (Tanjungpura Journal of Coaching Research, 2023)
The problem in this research is how the development of pencak silat Seliwa Betawi in Palembang City. The purpose of this research is to know the development and history of the entry of pencak silat from Betawi land to Palembang City. This research method uses qualitative descriptive research. Data validity techniques use degrees of trust (Credibility). Data collection techniques using observation, interviews and documentation. Sources of information are college administrators, local community leaders, martial arts students. Data analysis techniques in qualitative research consist of three simultaneous activity streams, namely data reduction, data exposure, and conclusion drawing and verification. The result of this research is that pencak silat Seliwa Betawi in Palembang City has experienced ups and downs in the pencak silat college environment due to the covid-19 pandemic factor that occurred. Suggestions in order to overcome the development problems that occur are from within the management of pencak silat Seliwa Betawi to increase its activity in holding activity agendas in the form of Betawi pencak silat competitions in order to make its own attraction in overcoming the ups and downs that occur.